A C2N/ZnSe heterostructure with type-II band alignment and excellent photocatalytic water splitting performance. (13th July 2021) - Rao, Yifan; Zhang, Fusheng; Zhu, Bao; Li, Hui; Zheng, Kai; Zou, Yongxian; Feng, Xiaoxia; Guo, Haojie; Qiu, Jian; Chen, Xianping; Yu, Jiabing
Abstract : A type-II C2 N/ZnSe heterostructure with strong light-absorption ability, high carrier mobility and low exciton binding energy, exhibits excellent photocatalytic water splitting performance Abstract : Photocatalytic water splitting technology, utilizing solar energy, water resources and suitable photocatalysts to produce hydrogen, holds great promise to deal with the current energy crisis. The construction of van der Waals heterostructures has shown great prospects in photocatalytic water splitting because of their unique physical mechanism. Here, using the first principles calculations, we comprehensively investigated a C2 N/ZnSe heterostructure constructed by C2 N and ZnSe monolayers, both of which have been successfully fabricated in the experiment. The results show that the C2 N/ZnSe heterostructure has favorable direct band gap and typical type-II band alignment, ensuring that the photogenerated electrons and holes are effectively separated. Moreover, the band edges of the C2 N/ZnSe heterostructure satisfy the energy level of water oxidation and reduction at pH = 0. In addition, carrier mobility and exciton binding energy calculations show that the C2 N/ZnSe heterostructure possesses ultrahigh electron mobilities and low exciton binding energy, indicating its high photocatalytic activity and low carrier recombination rate. Furthermore, the C2 N/ZnSe heterostructure exhibits a strong visible light-absorption ability (up to 2.35 × 10 5 cm −1 ), which is beneficial to improve its photocatalytic efficiency. Such excellent electronic and optical properties along with high carrier mobility and low exciton binding energy help the C2 N/ZnSe heterostructure to be a potential promising photocatalyst for future experimental design.